Analysis of the Level of Landslide Susceptibility in the Sakuli Latambaga Area, Southeast Sulawesi - Rasmita, Riza; Chaerul, Muhammad; Marzuki, Ismail; Gusty, Sri; Indrayani, Poppy; Sinardi, Sinardi (ASTONJADRO, 2024)
The vulnerability of landslides that occur in the Sakuli area, Kolaka Regency is related to topographic conditions which are dominated by mountains and hills, for this reason, research is needed as an effort to determine the level of vulnerability and determine disaster mitigation efforts against the danger of landslides. This type of research is quantitative descriptive by looking at the influence of each variable to analyze landslide-prone areas. The method used in this research is experimental analysis with direct observation in the field. From the research results, the vulnerability level value for the slope parameter was 0.83; with soil texture 0.408; for faults 0.86; value for regolith 0.363; with geological conditions 0.628; with a rainfall value of 0.3 and land use of 0.6, the accumulated value is that the research area is at a very vulnerable level with a value of 3.989. Therefore, this area really needs structural and non-structural mitigation to be able to protect and reduce the potential for landslides.